Maternal smoking around birth is associated with an increased risk of offspring constipation: Evidence from a Mendelian randomization study - Yong Shen+; Siqi Xie+; Yu Lin+; Yifan Fang; Bing Zhang; Jinna Zhang (Tobacco Induced Diseases, 2025)
Introduction This study aimed to investigate the association between maternal smoking around birth and the incidence of offspring constipation.